The Routledge companion to medieval English literature
1 online resource (xx, 479 pages)
Keywords: The Routledge Companion to Medieval English Literature offers a new, inclusive, and comprehensive context to the study of medieval literature written in the English language from the Norman Conquest to the end of the Middle Ages. Utilising a Trans-European context, this volume includes essays from leading academics in the field across linguistic and geographic divides. Extending beyond the traditional scholarly discussions of insularity in relation to Middle English literature and isolationism', this volume: Oversees a variety of genres and topics, including cultural identity, insular borders, linguistic interactions, literary gateways, Middle English texts and traditions, and modern interpretations such as race, gender studies, ecocriticism, and postcolonialism. Draws on the combined extensive experience of teaching and research in medieval English and comparative literature within and outside of anglophone higher education and looks to the future of this fast-paced area of literary culture. Contains an indispensable section on theoretical approaches to the study of literary texts. This Companion provides the reader with practical insights into the methods and approaches that can be applied to medieval literature and serves as an important reference work for upper-level students and researchers working on English literature.